2018
DOI: 10.1590/2177-9465-ean-2018-0205
|View full text |Cite
|
Sign up to set email alerts
|

Importance of families in care of individuals with mental disorders: nurses' attitudes

Abstract: Objectives: To characterize the attitudes of nurses working in primary health care on the importance of involving families in nursing care to the person with mental disorder. Method: A cross - sectional descriptive study with a quantitative approach performed with 328 nurses who work in primary health care in Porto, Portugal. Families Importance in Nursing Care - Nurses Attitudes (FINC-NA) scale was applied. Results: Scale scores were elevated, mean value was 85.9 (Maximum possible 104). The significant corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
4
10
0
4
Order By: Relevance
“…The results indicated that nurses consider themselves as having good attitudes towards families of NBs hospitalized in neonatal units. The score's general mean ranged from 75 to 86, similar to the findings of studies conducted in Europe (19)(20) and in Brazil (16,21) .…”
Section: Discussionsupporting
confidence: 78%
“…The results indicated that nurses consider themselves as having good attitudes towards families of NBs hospitalized in neonatal units. The score's general mean ranged from 75 to 86, similar to the findings of studies conducted in Europe (19)(20) and in Brazil (16,21) .…”
Section: Discussionsupporting
confidence: 78%
“…The main findings point out that nurses' attitudes are favorable to the involvement of families in caring for the person with MD, since the mean value of the IFNC-NA was 82.1 (SD=8.4). A close value of a recent study carried out with primary care nurses in Portugal found 85.9 (SD=9.6) (8) , in the dimensions: "Conversation/ coping partner family" 38.5 (SD=4.6) and "Family as a resource" 31.9 (SD=3.7); and higher in "Family: as a burden" 12.1 (SD=1.…”
Section: Discussionmentioning
confidence: 57%
“…In a literature review, primary health care nurses in Portugal showed supportive attitudes for the family of people with MD, and they believe that the decision to include them enhances their role as an enabling mediator in the care reorganization process (8) . In China, the attitudes of generalist nurses were less supportive concerning the importance of the family in nursing care, and aroused the perception, in families, that nurses are unable to offer the care that involves them.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supported by the scientific literature, considering a cross-sectional study carried out with 328 nurses working in primary care in Porto/Portugal, which pointed out a high degree of agreement on the part of professionals in relation to the importance of families in nursing care for people with mental disorders. 20 It was evidenced that the main care/monitoring resources are individual consultations with or without family member presence, therapeutic groups, individual psychotherapy and the psychiatric approach focused on medicalization, always performed within BHU. This finding corroborates the literature, emphasizing that even therapeutic groups seem to be centered on medication, as they are periodized according to the users' drug treatment progress.…”
Section: Discussionmentioning
confidence: 99%